Konflik Kekuasaan Dalam Novel Bungkam Suara Karya J.S. Khairen Berdasarkan Teori Marxis - Saputro, Hendro Tri; Wulandari, Ari (PT. Alahyan Publisher Sukabumi, 2025)
Power conflicts are very relevant to discuss in the context of current socio-political life. Social injustice and inequality are often caused by power. The aims of this research are, [1] To describe the power conflict in the novel Bungkam Suara, [2] To explain how Marxist theory can be used to understand the power conflict in the novel Bungkam Suara. This research uses a qualitative descriptive method. The primary data source in this research is the novel Bungkam Suara by J.S. Khairen. Secondary data sources in this research are information obtained through literature, journals and other sources that support and relate to the research topic. The data collection technique used is, reading and taking notes. The findings were then analyzed using Marxist theory on power conflicts. The results of this research conclude three power conflicts, namely, [1] individual conflict, [2] group conflict, [3] state conflict. Marxist theory can be used to understand power conflicts exercised and contested by various characters with different social, economic and political statuses. The interactions between these figures illustrate the dynamics of power conflict involving competition and manipulation in gaining power.